CRIMINAL POLICY OF KAZAKHSTAN IN THE FIELD OF INFORMATION SECURITY (Journal of actual problems of jurisprudence, 2018)
At present, information security in the Republic of Kazakhstan is at a rather low level, and in connection with this, the issues of this security are very acute. As you know, the development of the state and society as political and legal phenomena is always carried out in clearly defined historical and territorial factors that determine this development. At the same time, threats to the state, society and man are also in constant change, adequate for the development of society and the state. Modern world trends today signal the emergence of new formats of threats to the national security of Kazakhstan in the 21st century and among them the issue of information security is the most acute. The aim of scientific research it is been realization of analysis, orderly arguing the present, past and future state of informative safety of Republic of Kazakhstan in a context with international legal relationships in this sphere. The President of Kazakhstan in his annual message to the people of Kazakhstan on January 31, 2017 designates we must cultivate new industries that are created using digital technologies. This is an important complex task ... It is necessary to adapt our legislation to new realities ... Therefore, the government should keep the issue of IT sphere under special control. And the emphasis on informatization and information technologies is made by the President not one time, which speaks about the importance and information support, as well as information security of all important branches of state activity and high-level state tasks. That in turn explains so high importance and meaningfulness of science research and practical works in this direction. Scientific value the article have direct, because in modern society information and informative safety play if not above all, then one of leading roles and meaningful place, that prove the last events what be going on in the world and virtual the internet space for the last years.Practical meaningfulness of work is explained by a necessity by such works by society and practical and legal systems of the state.Key words: Criminal policy, President’s message, information, information security, information systems, international security, information technologies, computer crimes.